2020
DOI: 10.1091/mbc.e18-11-0715
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic actin-mediated nano-scale clustering of CD44 regulates its meso-scale organization at the plasma membrane

Abstract: We show a hierarchical organization of the adhesion receptor CD44 at multiple-length scales on the plasma membrane by studying the diffusion and clustering behavior of the protein.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…Integration of type-I formin within the multilayer tensegrity structure, CW-PM-AC continuum (Figure 6), controls the condensation and biochemical activities of formin and the architecture of cortical actin networks. By connecting with the PM by pinning sites, type-I formin might serve as mobile poles in a picket-fence actin meshwork, similar to the model that was proposed in the mammalian system (Figure 6) (Gowrishankar et al, 2012;Saha et al, 2015;Sil et al, 2020). Inter-linked cellular skeleton structures influence lateral mobility on the PM in mammalian cells.…”
Section: Regulation Of Formin Function By the Structural Integration mentioning
confidence: 65%
See 2 more Smart Citations
“…Integration of type-I formin within the multilayer tensegrity structure, CW-PM-AC continuum (Figure 6), controls the condensation and biochemical activities of formin and the architecture of cortical actin networks. By connecting with the PM by pinning sites, type-I formin might serve as mobile poles in a picket-fence actin meshwork, similar to the model that was proposed in the mammalian system (Figure 6) (Gowrishankar et al, 2012;Saha et al, 2015;Sil et al, 2020). Inter-linked cellular skeleton structures influence lateral mobility on the PM in mammalian cells.…”
Section: Regulation Of Formin Function By the Structural Integration mentioning
confidence: 65%
“…Together, the in vivo and in vitro results suggest that the higher-order clustering of formin might not be derived from the direct multivalent forminformin interactions, and additional unknown factors might be involved in recruiting and clustering formins to form nanoclusters and large punctae in vivo. It is conceivable that formin-based actin polymerization-driven nanoscale clustering, as observed for CD44 (Sil et al, 2020), may serve as a model for how the membrane-attached formin organizes itself into nanoclusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 is a cell surface adhesion molecule involved in cell-cell interactions, cell adhesion, and migration [ 1 ]. The main ligand of CD44 is hyaluronic acid (HA), a polysaccharide abundantly present in the extracellular matrix of mammals, yet it can bind to other components of the extracellular matrix and perform different functions depending on the structure of the protein it binds to [ 2 , 3 ]. It is composed of a distal extracellular amino-terminal domain (ECD), a stem region, a transmembrane domain (TM), and an intracellular cytoplasmic carboxy-terminal domain (ICD) ( Figure 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…Using super-resolution microscopy and/or single-molecule imaging, we and others have revealed that glycans can modulate the degree of clustering, mobility, and/or molecular interactions of different membrane receptors, thereby regulating their function. 9 12 …”
mentioning
confidence: 99%